2008
DOI: 10.1210/jc.2007-2185
|View full text |Cite
|
Sign up to set email alerts
|

Increased Toll-Like Receptor (TLR) 2 and TLR4 Expression in Monocytes from Patients with Type 1 Diabetes: Further Evidence of a Proinflammatory State

Abstract: Thus, we make the novel observation that TLR2 and TLR4 expression and signaling are increased in T1DM and contribute to the proinflammatory state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
278
3
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 332 publications
(318 citation statements)
references
References 28 publications
27
278
3
10
Order By: Relevance
“…Previously, we have shown that diabetic patients have increased monocytic TLR2 and TLR4 expression, which correlated to increased NF-kB activity, increased expression of downstream adapter proteins such as MyD88 and pIRAK, resulting in increased pro-inflammatory cytokines. 28 Similar findings were found when cells were treated in vitro under hyperglycemic conditions. 26 Thus, we suggest that abrogating inflammation in diabetic wounds using TLR2 as a target appears to be a reasonable approach to alleviate inflammation accelerating diabetic wound-healing process.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Previously, we have shown that diabetic patients have increased monocytic TLR2 and TLR4 expression, which correlated to increased NF-kB activity, increased expression of downstream adapter proteins such as MyD88 and pIRAK, resulting in increased pro-inflammatory cytokines. 28 Similar findings were found when cells were treated in vitro under hyperglycemic conditions. 26 Thus, we suggest that abrogating inflammation in diabetic wounds using TLR2 as a target appears to be a reasonable approach to alleviate inflammation accelerating diabetic wound-healing process.…”
Section: Discussionsupporting
confidence: 68%
“…Although TLR2 has been shown to be upregulated in NOD mice 30 and T1DM patients, 28 its role in contributing to the exacerbated inflammatory state of diabetic wounds is unclear. Furthermore, increasing experimental evidence indicates that engagement of the TLR2 by endogenous ligands may be a major trigger of inflammation in response to skin injury, ischemia, hemorrhagic shock, and ischemia/reperfusion injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MyD88 dependent signaling pathway activates both NF-κB and the mitogen-activated protein kinases (MAPK). Ultimately, activation of these molecules leads to an increase in the transcription of the pro-inflammatory cytokines TNFα and pro-IL-1β amongst others (Devaraj et al, 2008). As discussed previously, these pro-inflammatory cytokines are important components in contact allergen-dependent activation of DC and, thus, activation of NF-κB and MAPK might therefore be important in contact allergen-dependent activation of DC.…”
Section: Toll Like Receptorsmentioning
confidence: 86%
“…The type 1 diabetes patients also showed significant augmentation of downstream elements of TLR signaling and release of the proinflammatory cytokines IL-1 ␤ and TNF-␣ when compared with the control population. The release of proinflammatory cytokines strongly correlated with the increased expression of TLRs in the patient population that in turn strongly correlated with pathological signs like hemoglobin glycosylation (28). Proinflammatory cytokines like GM-CSF have been shown to augment MHCII and costimulatory molecules like CD86 and CD40 on monocytes (29).…”
Section: Professional Apcs Are the First Immune-sensitive Depots For mentioning
confidence: 97%